Desvendando as células tronco: o uso de aplicativo educacional como recurso pedagógico para ensino de biologia - Almeida, Alerson de Brito (2020)
From the zygote, in a process of cell division and differentiation, all cells that make up living organisms are formed. In these early stages of life, cells have unique capabilities, with the potential to differentiate into any existing type and are called stem cells. Despite being a recurring theme in the media, due to its applicability in health, this subject is little explored in books and high school classes in the discipline of Biology, lacking greater focus due to its relevance. Idealizing a proposal for school work with great potential to attract the attention of students, making them have more access to the stem cell theme, from literacy and scientific dissemination on the theme, as well as the use of new technologies in intra and extra-school environments , it was thought about the production of an educational application. In addition to the application's proposal to make the theme more accessible, it can also promote the student's role, since the use of this technology favors self-teaching, based on reading and solving problems. In the research, the action research method was used, which dealt with the quali / quantitative processes, analyzing abstract aspects, such as the perception of students and students (Profbio Nacional) about the subject, consisting of filling in online forms and experimenting with an educational application. Thus, the present work started with the making of the application, followed by its evaluation by students and professors who make up the three grades of High School. Participated in the research 28 students from the public state network of Paraíba, EEEFM José Pinheiro (Campina Grande-PB) and ECITE Monsignor José da Silva Coutinho (Esperança-PB). In relation to teachers, 20 master's students from the Professional Master's Program in Biology Teaching - PROFBIO, from different Brazilian states participated in the present work. After making the educational application, entitled “Unraveling the stem cells”, the link to access was made available via email and social networks (whatsapp) to the study population, as well as online forms to assess the application's capacity and potential about stem cells. Students and teachers received the link concurrently and had two weeks to carry out the evaluation. The students evaluated the App as a positive tool for the cognitive aspect, as well as in the construction of essential aspects in the education of the student, such as socialization, interaction, protagonism, motivation, cooperation and interactivity. The teachers, showed the instrument as extremely powerful to enrich the classes that address the chosen theme. These findings were evidenced through the comments of students and teachers, in the section of the available evaluation forms, in which they evaluated in a positive and satisfactory way the effectiveness of such a tool in the teaching of biology. It is hoped that the software presented here, can serve as an enhancement of educational activities and that it can inspire several colleagues, from the most different areas, to elaborate, search, innovate their classes, transmitting in the best possible way the knowledge so desired by our students, preparing them to exercise citizenship.